Challenges of Management of Stunned Myocardium Associated with Acute Subarachnoid Hemorrhage: A Case Report (Journal of National Institute of Neurosciences Bangladesh, 2018)
A 40 year old lady presented with headache and vomiting having no past history of hyper-tension, diabetes, smoking, alcohol or drug abuse. Computed Tomography (CT) scan of brain revealed sub-arachnoid haemorrhage in parasaggital frontal and lt. Sylvian fissure. Digital Subtraction Angiogram (DSA) was performed and revealed a small aneurysm (4x 2.5 x 2) mm in anterior communicating artery. After 12 hours of DSA patient complaints of sudden severe headache followed by unconsciousness. Repeat CT performed and revealed new onset rt. fronto-basal intra-cranial hematoma consistent with rebleed. On admission the patient was with normal Glasgow Coma Scale (GCS-15), Blood pressure (BP125/80mm/Hg), ECG & Echocardiogram. After rebleed patient developed low BP (50/35mmHg), GCS down gread (05), ECG showed sinus tachycardia with poor progression of R(V1-V3) wave, elevated cardiac Troponin –I(-4919.6 Pg). Then patient was given a regimen of ionotropic agent noradrenalin at dose 5mcg/kg/h. From day 3th of rebleed the patient was clinically improving, BP(120/84mmHg), GCS( 8), ECG normal, Cardiac Troponin-I- (790.8 Pg/dl). Then emergency endovascular ACOM coil embolization was done.Journal of National Institute of Neurosciences Bangladesh, 2018;4(2): 150-153